The Response and Pattern of Community Management for the Variety of Poverty Alleviation Assistance in the Fishermen's Village, across Belawan - Bakhrul Khair Amal (Budapest International Research and Critics University, 2018)
The method of social phenomenology is seen as appropriate to describe the dimensions of poverty so that reality will be found in the